Difusi Inovasi Program Budidaya Ikan Patin Dalam Meningkatkan Perekonomian Masyarakat - Nining Ayu Pratiwi (UIN Siber Syekh Nurjati Cirebon, 2024)
Diffusion innovation is a form of solution to the problem of poverty that occurs in various regions, one of which is in Koto Mesjid Village, Riau Province. By utilizing natural and human resources, innovations for cultivating freshwater fish using the catfish species have begun to be developed. Innovation diffusion activities in order to get out of underdevelopment and poverty are carried out with maximum effort from various parties involved such as innovators, local government, the community and investors. Cultivation, which was initially only a form of fulfilling food for the local community, has moved to cultivation as a form of effort to increase the economic level of the community, developing the creative economy more broadly. The diffusion innovation process outlined in the catfish cultivation program in Koto Mesjid Village needs to be analyzed further. So it can be discovered how the diffusion of innovations that are developed can bring local communities out of backwardness and poverty. The research method used in this journal article is a qualitative method. In this method, field observations and interviews were carried out with several related parties. The results of this research found that there were five stages of the innovation diffusion process carried out in the catfish cultivation program in Koto Mesjid Village. Starting from the knowledge stage by providing information about cultivation programs to the community. Persuasion is where the community considers the innovation program with its role as adopter. The decision stage is where the community decides to accept the catfish cultivation innovation program. Then, implementation is at this stage where the community carries out these cultivation activities. The last one is confirmation, namely the implementation of an evaluation of cultivation activities and the community is also given the option to stop or continue the cultivation program.